Stability and luminescence studies of Tm and Er implanted ZnO single crystals - Rita, E.
Zinc oxide single crystals were implanted with Tm and Er ions in a wide range of fluences. For both types of ions RBS/channeling shows for the as-implanted state the same minimum yield as for the host. Damage recovery becomes significant for annealing above 750 °C and is almost complete at 1050 °C. Implantation damage decreases for implantations at mild temperatures (450 °C) and is also highly reduced for 〈 0 0 0 1 〉 aligned implantations: under this condition the measured minimum yield is about one order of magnitude lower compared to the random implantations. The RE ions start to diffuse towards the surface above 900 °C and about 80% of them have segregate to the surface after 90 min annealing at 1050 °C. A small fraction of the ions retained in the implanted region is located in regular lattice sites. In the as-implanted state the optical activity of the RE ions is highly quenched by the implantation defects. For all the RE studied, diffusion to the surface destroys the luminescence. Photoluminescence (PL) studies for Er implantations reveal in the as-implanted and annealed samples the presence of a weak emission near 1.54 μm due the 4I13/2 → 4I15/2 transition of the Er3+ ions